Metabolomics investigations of the effect of drugs on mammalian cells - Ngamratanapaiboon, Surachai (2017)
Cell-based metabolomics using LC-MS systemizes the study of the uniqueness of small-molecule metabolite (metabolomes) profiles in cellular processes. Cell-based metabolomics can potentially be used in many applications for the study of biological perturbation from stimulants in cellular pathways. The advantages of cell-based metabolomics include ease of control and interpretation when compared to the study of human subjects and animal models. Furthermore, this method can decrease some highly challenging problems that occur in genomics, transcriptomics and proteomics. Nowadays, cell culture in metabolomics studies has been used in many applications. These include cell culture and bioreactor optimisation, phenotype classification, stimulant testing effect, target and toxicity analysis, metabolic networks determination and modelling, and biomarker and drug target discovery. In this study, the reverse phase-liquid chromatography-mass spectrometry and hydrophilic interaction chromatography-mass spectrometry for comprehensive metabolic profiling well suited to the untargeted analysis of non-polar and polar metabolites in mammalian cells were developed, optimized and validated. These methods can separate and detect most of hydrophobic and polar metabolites that are normally found in mammalian cell lines. After that the LC-MS methods were applied to assess the effects of drugs with known and unknown cellular metabolic effects on three mammalian cell lines, namely HMVECs for antipsychotics experiment, MCF-7 cells for cordycepin experiment and MIN6 cells for fluoxetine experiment by using untargeted metabolic profiling. The global effects of antipsychotics at high therapeutic dosage in HMVECs were investigated. The results support for the toxicity hypothesis with measurements that confirm previous findings and reveal the exact biological pathways of antipsychotic-altered BBB functions. It was found that antipsychotics may affect the bioenergetics pathway due to mitochondrial dysfunction resulted in ketoacidosis and inducing oxide stress by reactive oxygen species generation. In the MCF- cell experiment, the results of the untargeted metabolite profiling demonstrated the clear anti-breast cancer effects of cordycepin and pentostatin. By investigating the metabolite profiles, clear synergistic effects of cordycepin and pentostatin combined in comparison to cordycepin activity alone in MCF-7 cells was observed. Furthermore, the pathway analysis indicated that anti-breast cancer activity was mainly responsible for alterations in purine and pyrimidine metabolism and bioenergetics. Additionally, cordycepin may be involved in the inhibition of cell proliferation and differentiation, and the activation of cell apoptosis. The last experiment on MIN6 cells, the developed and optimized HILIC-MS approach in order to determine the biological pathways which are impaired by fluoxetine on glucose-stimulated insulin secretion on MIN6 cell lines was performed. It is found that fluoxetine may impair glycolysis, TCA and fatty acid metabolism on MIN6 cell lines. Moreover, it is also reveal that the alteration of biological pathways on MIN6 cells by known ETC inhibitors (rotenone (Complex I inhibitor, antimycin (Complex III inhibitor) and azide (a complex IV inhibitor). From comparison with these ETC inhibitors, it is found that fluoxetine may have the same effect pattern with azide.